Playing the cards you're dealt - Johnson, Varian (Scholastic Inc., 2023)
As ten-year-old Anthony "Ant" Joplin prepares for the Oak Grove annual spades tournament, a tradition for his South Carolina family, he is feeling the pressure to make his father and brothers proud of him. When his best friend Jamal can no longer be his partner, he begins secretly working with new girl Shirley, who has mad card skills, but who he thinks his father won't approve of because she's a girl. As his father's alcoholism deteriorates and a gambling addiction surfaces, Ant begins to question his father's notions about masculinity and decides for himself what makes a man.